2015
DOI: 10.1302/0301-620x.97b4.34577
|View full text |Cite
|
Sign up to set email alerts
|

Coxa profunda in the diagnosis of pincer-type femoroacetabular impingement and its prevalence in asymptomatic subjects

Abstract: In many papers, the diagnosis of pincer-type femoroacetabular impingement (FAI) is attributed to the presence of coxa profunda. However, little is known about the prevalence of coxa profunda in the general population and its clinical relevance. In order to ascertain its prevalence in asymptomatic subjects and whether it is a reliable indicator of pincer-type FAI, we undertook a cross-sectional study between July and December 2013. A total of 226 subjects (452 hips) were initially screened. According to strict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
2
22
1
Order By: Relevance
“…However, coxa profunda sign was found as a common radiographic finding even in healthy and asymptomatic subjects, so it was considered as a benign alteration in the hip morphology as well as a nonspecific radiographic indicator of pincer type FAI. [16,17] The findings of our study including limited number of cases are not compatible with the ones of the previously mentioned studies. We believe that coxa profunda sign needs to be revisited in larger FAI case series including symptomatic and surgically treated patients.…”
Section: Discussioncontrasting
confidence: 97%
“…However, coxa profunda sign was found as a common radiographic finding even in healthy and asymptomatic subjects, so it was considered as a benign alteration in the hip morphology as well as a nonspecific radiographic indicator of pincer type FAI. [16,17] The findings of our study including limited number of cases are not compatible with the ones of the previously mentioned studies. We believe that coxa profunda sign needs to be revisited in larger FAI case series including symptomatic and surgically treated patients.…”
Section: Discussioncontrasting
confidence: 97%
“…1,2 Specifically, there has not been any study on whether or not the hip capsule is thickened in diseased hips requiring surgery compared with normal hips.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Diesel et al found coxa profunda in 77% of asymptomatic volunteers, as demonstrated on radiography, with an increased prevalence in women. 37 Nepple et al reported evidence of coxa profunda in 76% in a retrospective study with 33 asymptomatic patients who received radiographs for nonhip-related indications. 38 This led them to conclude that coxa profunda is a nonspecific finding and not useful in the diagnosis of pincer FAI.…”
Section: Discussionmentioning
confidence: 99%